Characterizing the role of SLC3A2 in the molecular landscape and immune microenvironment across human tumors - He, Jiajun; Liu, Dong; Liu, Mei; Tang, Rong; Zhang, Dongqing (Frontiers in Molecular Biosciences, 2022)
Background: Inducing ferroptosis in human tumors has become a potential strategy to improve the prognosis of patients, even in those with chemotherapeutic resistance. The xCT complex is a major target for ferroptosis induction, constituted by SLC7A11 and SLC3A2. The role of SLC7A11 in cancer has been widely studied in recent years. However, related research studies for its partner SLC3A2 are still rare. Methods: Bulk transcriptome, single-cell sequencing, and immunohistochemical staining were analyzed to explore the expression distribution of SLC3A2. Clinical outcomes were referred to uncover the relationship between SLC3A2 expression and patients’ prognosis. Immune cell infiltration was estimated by multiple deconvolution algorithms. The effect of SLC3A2 on the proliferation and drug resistance of cancer cell lines was evaluated by DEPMAP. Results: Upregulated SLC3A2 may have an adverse effect on the survival of multiple cancers such as lower-grade glioma and acute myeloid leukemia. SLC3A2 expression is indispensable for multiple cell lines’ proliferation, especially for ESO51 (a cell line for esophageal cancer). In addition, SLC3A2 expression level was related to the remodeling of the immune microenvironment in cancers and some immune checkpoints such as PD-1 and PD-L1, which were potential therapeutic targets in many distinct cancers. Conclusion: Our study systematically elucidated the role of SLC3A2 in the survival of cancer patients and the potential immunotherapeutic response. Few molecular mechanisms by which SLC3A2 regulates anti-tumor immunity have been clarified in the present study, which is the main limitation. Future research into the biological mechanism could further help with targeted treatment for cancer patients.